Decoding the Semantic Marvels of the Quran: The Intricate Meanings of 'Home' in Islamic Architecture - Yulianto, Yulianto (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This research examines the i’jaz (scientific miracles) of the Quran concerning the semantic field of the word al-baytu within the study of Islamic architecture, a topic that has not been previously explored. The study draws data from Quranic verses containing the term al-baytu and the semantic field of the word al-baytu, such as al-manzilu, al-maskanu, and others. The data collected is then interpreted through the lens of i’jaz (scientific miracles) of the Quran following the terminological framework of the Quranic lexicon. The interpreted results are subsequently analyzed using componential analysis. Based on the results and discussion, it is concluded that the i’jaz (scientific miracles) of the Quran in the semantic field of bayt in the Quran includes terms such as al-maskanu, al-baytu, al-qosru, al-manzilu, ad-dāru, al-qoryatu, and al-madīnatu. Al-maskanurefers to a single dwelling that provides comfort, unlike al-baytu, which also signifies a single dwelling but does not or cannot provide comfort. Al-maskanu is akin to the concept of